Determination of bismuth in biological samples using on-line flow-injection microwave-assisted mineralization and precipitation/dissolution for electrothermal atomic absorption spectrometry - Burguera, J.L.; Burguera, M.; Rivas, C.; Rondon, C.; Carrero, P.; Gallignani, M. (Talanta (Oxford), 1999)
An on-line automated flow injection system with microwave-assisted sample digestion for the electrothermal atomic absorption spectrometric determination of bismuth in biological materials is described. After the exposure of the sample to microwave radiation, the analyte was subject to a precipitation/dissolution process. Bismuth was precipitated with the stannite ion in basic medium and collected on the walls of a knotted coil, while the other matrix components flowed downstream to waste. The precipitate was dissolved with nitric acid and a sub-sample was collected in a capillary of a sampling arm assembly, to introduce 20 μl volumes into the graphite tube by means of positive displacement with air through a time-based injector. The analytical figures of merit were first evaluated by filling the sampling arm with a standard solution of bismuth and thereafter injecting aliquots of this solution into the atomizer. The calibration graph was linear from the detection limit (8 pg) to 1.2 ng of bismuth. The sensitivity was of 26.8 μg l −1 for 0.2 A-s and the characteristic mass ( m o) was of 11.8 pg/0.0044 A-s. The precision of the method, evaluated by replicate analyses of solutions containing 20 and 200 pg of bismuth, were 5.5 and 3.0% ( n=10), respectively. When solutions were introduced in the flow system here described, the calibration graph was linear in the range 0.04–6.0 μg l −1, which means that a preconcentration factor of 10 was obtained for bismuth. The precision slightly deteriorated, e.g. the replicate analysis of solutions containing 1 and 10 pg of bismuth were 7.1 and 5.3% ( n=10), respectively. However, the recoveries values obtained with urine and whole blood bismuth spiked samples were over 96.5% and the agreement between observed and certified values was good.